Mercury pollution : a transdisciplinary treatment - Newman, Michael C.; Zuber, Sharon L. (CRC Press, 2012)
"Mercury is the gravest chemical pollutant problem of our time, and this is the first publication that has undertaken holistic coverage of this truly global issue. This book is an outstanding product of the innovative Global Inquiry Groups (GIG) process of interdisciplinary collaboration, which brings together the physical sciences, social sciences, and the humanities including the study of media, visual, and literary arts, uniquely enabling us to look at and understand mercury from the many perspectives needed in order to grasp the problem in its totality. This book clarifies how we are all connected to mercury, how we take it in through the food we eat and the air we breathe, and how we release it as a consequence of our lifestyle. It tells us about the relationship people have had with mercury from ancient to modern times. It tells us how people have given artistic expression to the ravages of mercury, touching our emotions and changing us. It refers to the social injustice of mercury pollution. This book is an attempt to communicate beyond the walls of academia to a larger audience. Therefore, on behalf of the authors of chapters within this book and the mercury group, I invite you to explore metal mercury from the varied perspectives of history, science, sociology, government, writing, and art. Each chapter represents a disciplinary thread from the GIG. Our goal was to weave these interdisciplinary threads into a tapestry that presents a more complete picture of the effects of mercury pollution and to provide new ways to think about the environment and our individual responsibility toward each other and our earth"--